2023
DOI: 10.5551/jat.63695
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Remnant Cholesterol with Endothelial Dysfunction and Subclinical Atherosclerosis in a Check-Up Population in China

Abstract: Aim: Vascular endothelial function and atherosclerosis are known to be important risk factors for cardiovascular disease. However, it remains unknown whether remnant cholesterol (RC) correlates with vascular endothelial function and atherosclerosis as represented by flow-mediated vasodilation (FMD) and brachial-ankle pulse wave velocity (baPWV). Therefore, in this study, we aimed to investigate this in the general population. Methods:In this study, we examined 13,237 subjects who have undergone blood lipid, FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Excessive lipids and cholesterol bind to the arterial intima and accumulate in the arterial wall, causing oxidative and nitrosative stress that leads to chronic inflammation of the vascular wall and other mechanisms that increase vascular resistance, thereby causing or accelerating arteriosclerosis [ 7 , 37 ]. Yang et al's study found that RC was negatively correlated with flow-mediated vasodilation (FMD), representing endothelial function, and positively correlated with brachial-ankle pulse wave velocity, indicating that RC causes ED and subsequent arteriosclerosis [ 5 , 38 , 39 ]. In a study of patients with familial dysbetalipoproteinemia (FD) that increases RC levels, it was found that arterial wall and cell inflammation increased in FD patients.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive lipids and cholesterol bind to the arterial intima and accumulate in the arterial wall, causing oxidative and nitrosative stress that leads to chronic inflammation of the vascular wall and other mechanisms that increase vascular resistance, thereby causing or accelerating arteriosclerosis [ 7 , 37 ]. Yang et al's study found that RC was negatively correlated with flow-mediated vasodilation (FMD), representing endothelial function, and positively correlated with brachial-ankle pulse wave velocity, indicating that RC causes ED and subsequent arteriosclerosis [ 5 , 38 , 39 ]. In a study of patients with familial dysbetalipoproteinemia (FD) that increases RC levels, it was found that arterial wall and cell inflammation increased in FD patients.…”
Section: Reviewmentioning
confidence: 99%
“…Remnant cholesterol (RC) has emerged as a potential cause of this residual risk [4]. The relationship between RC, arteriosclerosis, and CVD is well-established [2,3,5,6]. Lifestyle interventions and drug therapies have proven effective in reducing RC levels, providing a new therapeutic approach for the prevention and treatment of related CVD.…”
Section: Introductionmentioning
confidence: 99%
“…FMD = [(maximum brachial artery diameter—resting brachial artery diameter)/resting brachial artery diameter] × 100%. This method has been validated previously ( 17 ).…”
Section: Methodsmentioning
confidence: 99%